(untitled) (Journal of International Studies, 2014)
The Mongolian economy has been producing a strong double digit growth. This presentation reviews some key macroeconomic indicators, such as GDP growth, inflation etc., and briefly outlines the mandate of the Bank of Mongolia and monetary policy guidelines for 2015.